Yield performance and economics of wheat varieties under organic farming - YADAV, S K; SHARMA, S K; CHOUDHARY, ROSHAN; JAIN, R K; JAT, GAJANAND (The Indian Journal of Agricultural Sciences, 2020)
Area under organic cultivation of wheat is increasing in India. Information on the yield performance and economic suitability of wheat varieties for organic farming in different agro climatic conditions is lacking. The present two year study was carried out during 2015 and 2016 to observe the yield performance of different varieties of bread, durum and local wheat under sub-humid conditions of southern plains and Aravalli Hills of Rajasthan. Results revealed that among the 12 varieties of wheat tested under organic production system, the maximum grain yield (56.39 q/ha) was obtained from durum wheat variety HI-8713 having 53.50 grains/ear followed by bread wheat variety MP-3288 (45.74 q/ha grain yield) bearing 51.67 grains/ear during both the years. Under organic production system the durum wheat variety HI-8713 recorded maximum net profit of ₹ 170700/ha which was higher by ₹ 68247, ₹ 79436 and ₹ 85055 over the commonly grown wheat varieties Raj-4037, Raj-3765 and Raj-4120, respectively.